Analysis of the Implementation of Sales Accounting Systems with Based Payment Transactions Fintech MSMEs Telukjambe Karawang - Zalfahmi, Raihan; Sujaya, Fista Apriani; Trisyanto, Ade (Fakultas Ekonomi dan Bisnis Universitas Ibn Khaldun Bogor, 2024)
The development of digital technology has brought transformation in society. Financial technology or fintech is a risk-taking service that currently helps many people, this technology is used in the economic and financial sectors. Fintech comes in various forms to help people overcome their financial and business problems. Additionally, fintech is becoming increasingly popular due to its fast and simple methods and services. This research aims to analyze the application of fintech in helping the development of micro, small and medium enterprises. The method used is descriptive research with a qualitative approach. Data collection was obtained through interviews and observation. The data obtained is in the form of primary and secondary data. The results of this research state that the implementation of a fintech-based sales accounting system in payment transactions in MSMEs helps buying and selling transactions so that the payment system becomes more efficient and economical but remains effective. All interviewees from all samples have sufficient financial literacy because they have general knowledge about fintech payments, confidence and skills in using fintech payments.